Prenatal and Postpartum Home Visits and Postpartum Contraceptive Use: A Cross-Sectional Analysis - Archer, Sydney R; Wall, Kristin M; Kottke, Melissa J (Journal of women's health (Larchmont, N.Y. 2002), 2025)
The postpartum period is a time of unmet contraceptive need for many women. Home visits by a health care worker during pregnancy or after delivery could increase postpartum contraceptive use and decrease barriers to accessing postpartum care. This study investigated the association between prenatal or postpartum home visits and postpartum contraceptive use using a large sample of U.S. women from 41 states. We conducted a cross-sectional analysis using weighted survey data from the 2012-2015 Phase 7 Pregnancy Risk Assessment and Monitoring Systems Core and Standard Questionnaires. Descriptive statistics and multivariate logistic regression models estimated the association between having a prenatal or postpartum home visit and self-reported postpartum contraceptive use. Of 141,296 women, approximately 21% received prenatal or postpartum home visits and 79% used postpartum contraception. After controlling for sociodemographic, reproductive, and health-related factors, women who received prenatal or postpartum home visits had a higher odds of postpartum contraception use (adjusted odds ratio 1.08, 95% confidence interval 1.02-1.15, = 0.009). Women who were older, were minority race, had less than a high school education, received inadequate prenatal care, experienced partner abuse during pregnancy, or experienced multiple stressors during pregnancy had a lower odds of postpartum contraception use in adjusted analyses controlling for home visitation. Given the benefits of recommended interpregnancy intervals to both the mother and the baby, adding formal contraceptive counseling and offering a variety of postpartum contraceptive methods in the home could further strengthen home visitation programs in the United States and may support women in achieving their reproductive goals.